Multidisciplinary protocols are an important part of enhanced recovery after major lower extremity amputation - Campat, Christian; O’Banion, Leigh Ann (Frontiers in Surgery, 2025)
Major lower extremity amputation (MLEA) remains a high-risk procedure with significant implications for patient morbidity, mortality, and long-term functional independence. Optimizing outcomes for this vulnerable population requires a comprehensive, multidisciplinary approach guided by evidence-based perioperative care pathways. Enhanced Recovery After Surgery (ERAS) protocols offer a structured framework to improve recovery trajectories by standardizing key elements of care. This review examines the application of ERAS principles to the MLEA population, synthesizing current literature on preoperative assessment and patient selection, multimodal analgesia, early mobilization strategies, and coordinated post-discharge planning. By integrating findings from consensus statements and pilot studies, we demonstrate how tailored ERAS-based multidisciplinary protocols can reduce complications, enhance functional recovery, and promote equity in outcomes. The development and implementation of such structured care pathways represent a critical step toward improving the standard of care for patients undergoing major lower extremity amputation.